Eligibility of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) modulator therapies: cohort of cystic fibrosis registry of Türkiye - Erdal, Meltem Akgul; Buyuksahin, Halime Nayir; Sen, Velat; Kilinc, Ayse Ayzit; Cokugras, Haluk; Dogan, Guzide; Dogru, Deniz (Turkish J Pediatrics, 2025)
Background. Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) variants are essential for determining eligibility for CFTR modulator drugs (CFTRms). In contrast to Europe and the USA, the treatment eligibility profile of cystic fibrosis (CF) patients in T & uuml;rkiye is not known. In this study we aimed to determine the eligibility of CF patients in T & uuml;rkiye for the CFTRms. Methods. The Cystic Fibrosis Registry of T & uuml;rkiye (CFrT) data was used to determine the age of patients in the year 2021 and the genetic variants they were carrying. Age- and CFTR-variant appropriate modulator therapies were determined using the Vertex (R) algorithm. Results. Among a total of 1930 registered patients, CTFR gene analysis was performed on a total of 1841 (95.4%) patients. Mutations were detected in one allele in 10.7% (198 patients), and in both alleles in 79% (1455 patients) of patients. A total of 855 patients (51.7% for whom at least 1 mutation was detected) were eligible for the drugs. The most appropriate drug among genotyped patients was found to be elexacaftor/tezacaftor/ivacaftor for 486 patients (26.4%), followed by ivacaftor for 327 patients (17.7%) and lumacaftor/ivacaftor for 42 patients (2%). Conclusions. Only half of patients registered in CFrT were eligible for CFTRms, which is a significant difference from the CFTR variant profile seen in USA and Europe. However, access to treatment is hampered for some patients whose genes are not analysed. Further studies in CF populations, where rare mutations are relatively more common, will contribute to the field of CFTR modulator treatments for such rare mutations.
Keywords: cystic fibrosis; cystic fibrosis transmembrane conductance regulator; CFrT registry; modulator; treatment